Neuroprotective effects of coenzyme Q10 on neurological diseases: a review article - Bagheri, Shokufeh; Haddadi, Rasool; Saki, Sahar; Kourosh-Arami, Masoumeh; Rashno, Masome; Mojaver, Ali; Komaki, Alireza (Frontiers in Neuroscience, 2023)
Neurological disorders affect the nervous system. Biochemical, structural, or electrical abnormalities in the spinal cord, brain, or other nerves lead to different symptoms, including muscle weakness, paralysis, poor coordination, seizures, loss of sensation, and pain. There are many recognized neurological diseases, like epilepsy, Alzheimer’s disease (AD), Parkinson’s disease (PD), multiple sclerosis (MS), stroke, autosomal recessive cerebellar ataxia 2 (ARCA2), Leber's hereditary optic neuropathy (LHON), and spinocerebellar ataxia autosomal recessive 9 (SCAR9). Different agents, such as coenzyme Q10 (CoQ10), have neuroprotective effects against neuronal damage. Online databases, such as Scopus, Google Scholar, Web of Science, and PubMed-MEDLINE were systematically searched until December 2020 using keywords, including review, neurological disorders, and CoQ10. CoQ10 is endogenously produced in the body and also, can be found in supplements or foods. CoQ10 has antioxidant and anti-inflammatory effects and plays a role in energy production and mitochondria stabilization, which are mechanisms, by which CoQ10 exerts its neuroprotective effects. Thus, in this review, we discussed the association between CoQ10 and neurological diseases, including AD, depression, MS, epilepsy, PD, LHON, ARCA2, SCAR9, and stroke. In addition, new therapeutic targets were introduced for next drug discoveries.